The Measurement of Efficiency and Analysis of Factors Affecting Conventional Commercial Banks in Indonesia - Aziz, Lukmanul Hakim; Manurung, Adler Haymans; Sembel, Roy; Imron, Ali (Management Science Research Journal, 2023)
The purpose of this research is to measure the level of efficiency of conventional commercial banks in Indonesia with input variables that are thought to influence output variables using non-parametric methods using the Data Envelopment Analysis (DEA) model and then to analyze the factors that affect the levels of bank efficiency. The object of this study consisted of 12 (twelve) Conventional Commercial Banks in Indonesia which were analyzed from 2012 to 2021. Overall, the results show that the level of efficiency of Conventional Commercial Banks in Indonesia during the period of this study, has not yet reached an optimal level of effectiveness. The factors that significantly affect the level of efficiency of conventional commercial banks are Concentration Ratio 4 (CR4), Market Share (MS), Lerner Index (LI), Loan to Deposit Ratio (LDR) and Capital Adequacy Ratio. (CAR). While the factors that do not affect the level of efficiency of conventional commercial banks are Return on Assets (ROA) and Non-Performing Loans. (NPL).